Amorphous silicates as a record of solar nebular and parent body processes—A transmission electron microscope study of fine‐grained rims and matrix in three Antarctic CR chondrites. (22nd June 2020) - Vollmer, Christian; Pelka, Mandy; Leitner, Jan; Janssen, Arne
Abstract: Renazzo‐type (CR) carbonaceous chondrites belong to one of the most pristine meteorite groups containing various early solar system components such as matrix and fine‐grained rims (FGRs), whose formation mechanisms are still debated. Here, we have investigated FGRs of three Antarctic CR chondrites (GRA 95229, MIL 07525, and EET 92161) by electron microscopy techniques. We specifically focused on the abundances and chemical compositions of the amorphous silicates within the rims and matrix by analytical transmission electron microscopy. Comparison of the amorphous silicate composition to a matrix area of GRA 95229 clearly shows a compositional relationship between the matrix and the fine‐grained rim, such as similar Mg/Si and Fe/Si ratios. This relationship and the abundance of the amorphous silicates in the rims strengthen a solar nebular origin and rule out a primary formation mechanism by parent body processes such as chondrule erosion. Moreover, our chemical analyses of the amorphous silicates and their abundance indicate that the CR rims experienced progressive alteration stages. According to our analyses, the GRA 95229 sample is the least altered one based on its high modal abundance of amorphous silicates (31%) and close‐to‐chondritic Fe/Si ratios, followed by MIL 07525 and finally EET 92161 with lesser amounts of amorphous silicates (12% and 5%, respectively) and higher Fe/Si ratios. Abundances and chemical compositions of amorphous silicates within matrix and rims are therefore suitable recorders to track different alteration stages on a submicron scale within variably altered CR chondrites.